The Traffic Characteristic Analysis of Jalan Ciater Raya South Tangerang, Indonesia - Achmad Oktobrianto; Andri Irfan Rifai; Adinda Fajarika Akhir (International Journal Labs, 2022)
Jalan Ciater Raya Serpong, South Tangerang City, has criteria for a 4/2 D road with a width of 3.5 m per lane. During peak hours, this road experiences congestion with a length of more than 1.5 km. LHR Jalan Ciater Raya = 25296 pcu/day with peak peak peak hours at 07:00-08:00 am and 6:00 pm-8:00 pm. The research data were obtained from surveys and direct traffic observations. By analyzing road characteristics using the Greenshield and Greenberg models, the relationship between the volume, speed, and density of road traffic can be found, so optimal values of Vm, Qm, and Dj can be found.